Archaeologists and the dead : mortuary archaeology in contemporary society - Williams, Howard, 1972-; Giles, Melanie (Oxford University Press, 2016)
This volume addresses the relationship between archaeologists and the dead, through the many dimensions of their relationships: in the field (through practical and legal issues); in the lab (through their analysis and interpretation); and in their written, visual and exhibitionary practice - disseminated to a variety of academic and public audiences. Written from a variety of perspectives, its authors address the experience, effect, ethical considerations, and cultural politics of working with mortuary archaeology. Whilst some papers reflect institutional or organisational approaches, others are more personal in their view: creating exciting and frank insights into contemporary issues which have hitherto often remained 'unspoken' amongst the discipline. Reframing funerary archaeologists as 'death-workers' of a kind, the contributors reflect on their own experience to provide both guidance and inspiration to future practitioners, arguing strongly that we have a central role to play in engaging the public with themes of mortality and commemoration, through the lens of the past. Spurred by the recent debates in the UK, papers from Scandinavia, Austria, Italy, the US, and the mid-Atlantic, frame these issues within a much wider international context which highlights the importance of cultural and historical context in which this work takes place.